The Influence Of Motivation, Job Training, And Information Technology To Performance Of Employee Maxone Hotel & Delia Resort Makassar - Azis, Azhar Asy’ari; Muhibuddin, Andi; Saleh, Muhammad Yusuf (Postgraduate Bosowa University Publishing, 2018)
This study aims to determine the effect of motivation, job training and information technology on the performance of employees of Maxone Hotel & Resort Delia Makassar. The research method used is a quantitative method, the data of this study were analyzed using SPSS 24 software. The number of samples in this study were 73 employees. The results showed that motivation had a positive and significant effect on employee performance with unstandardized coefficients 0,371 with tcount 3,42 8> t-table 0,235 with a significance level of 0,001 < 0,05; Job training has a negative but not significant effect on employee performance with unstandardized coefficients 0.168 with t-count of 1.549 > t-table 0.235 with a significance level of 0.126 > 0.05; Information technology has a positive and significant effect on employee performance with unstandardized coefficients 1,549 with t-count 3,727 > t-table 0,235 with a significance level of 0,000 < 0,05; motivation, job training and information technology have a positive and significant effect on employee performance with F-count 46.734 > F-table 2.74 with a significance level of 0.000 < ? 0.05.